Perancangan Antena Smartphone Mimo 8X8 Multi Layer Untuk Jaringan Komunikasi Nirkabel 5G - Franatha, Vickri Wira; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Currently, research on MIMO microstrip antennas to support fifth generation (5G) technology is increasing. This is because high data rate is required. A 28 GHz frequency is one of the mobile allocation frequencies approved by the Federal Communication Commission (FCC). In this research, Multiple Input Multiple Output (MIMO) 8x8 smartphone antenna working on 28 GHz using Computer Simulation Technology (CST) Microwave Studio simulation software is designed. The antenna is designed with 4 layers of the same substrate using aperture coupled technique. The aperture coupled technique allows the antenna to generate large bandwidth. Based on simulation result data, This antenna gives the result of parameter simulation values such as bandwidth impedance 2.38 GHz (8.5%), return loss -45.912 dB, Voltage Standing Wave Ratio (VSWR) 1.01 and gain 12.5 dB at 28 GHz. The design of antenna is expected to be applied at mobile smartphones and work on millimeterwave mobile communications systems in the future.Keywords: MIMO, Aperture Coupled, Milimeterwave